Parto de ideias: a epistemologia platônica como metáfora sexual - Bail, Renilson (Revista Archai, 2025)
This article intends to interpret the meaning of the sexual metaphor present in the characterization of the maieutic art of the Theaetetus as well as in the description of the psychically fecund lovers of the Symposium. Even though the “Socratic method” is illustrated as a practice comparable to birth giving, and Socrates’ activity is compared to midwifery, the text also mentions other successive stages of human reproduction, and other functions related to erotic phenomena are attributed to Socrates. Notably, in the Symposium, the character Diotima describes the educational practice of two special kinds of lovers through an analogy that also alludes to sexual imagery. The two analogies are scrutinized and then the article problematizes the meaning of terms associated with the verb κυεῖν in selected passages of the two dialogues, showing that the meaning varies between “being pregnant” and “being fecund”. Finally, the article presents the object of gestation and abortion at the intellectual level through the notion of γένος, and proposes that, in the ethical level, the educational lover and the one he educates conceive of and generate the excellences as a product of a process analogous to the natural fecundity of a human pair.